Analisis Jangka Panjang dan Jangka Pendek Variabel Makroekonomi dalam Upaya Menstabilkan Inflasi di Indonesia - Husnun Aziza Dg Silasa (Jurnal Ilmiah Mahasiswa FEB, 2015)
The movement of inflation in Indonesia have considerable fluctuation high and persistent. An understanding of the characteristics and sources of shocks that could trigger inflation can be used as a basis for formulating an effective monetary policy and consistent stability control inflation, as the final destination. This study aimed to analyze the macroeconomic variables underlying causes of inflation and see what variables are most dominate in the long term and short term, using the Error Correction Model (ECM). Data in the form of time series during the period 2002: Q1-2015: Q4 and publications obtained from Bank Indonesia and the Central Bureau of Statistics.The results of this study indicate that according to estimates ECM, long-term inflation in Indonesia is significantly affected by two independent variables, namely the BI rate and household consumption and both variables have a negative influence. In the short term, the increase in the BI rate and household consumption have a significant and positive influence on the rate of inflation. Based on the results of the estimation model of long-term and short-term inflation is influenced by the contribution of changes in the BI rate.Keywords: Inflation, BI rate, money supply, exchange rates, household consumption, ECM.